Reproductive Pattern and Performance of Nanny Goats in Kerala - Krishna Kumar G (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1992)
A study to elucidate the reproductive pattern and performance of nanny goats under the agroclimatic conditions of Kerala conducted on a flock of 154 nanny goats of mixed genotype, Malabari, Saanen x Malabari and Alpine x Malabari, maintained under the All India Co – ordinated Research Project on goats for milk, Kerala Agricultural University, has revealed the following results and conclusions. The method adopted was detection of oestrus twice a day using a vasectomised buck and by clinical examination. On detection, all animals of good reproductive health were bred artificially with freshly collected semen extended in Tris buffered yolk extender and preserved at low temperature. A group of animals were given a second insemination after seven hours of the first insemination for a comparison of the success rate to single and double inseminations during a heat. Following breeding, the duration of gestation, durations of stages of parturition, presentation of kids, incidence of multiple birth and secondary sex ratio were also recorded. Daily record of maximum and minimum temperature for a period of one year of the study was maintained. The period was divided into four quarters almost in agreement with the four natural seasons and the conceptions during each of the quarters were related with their secondary sex ratio and birth weight records to know the influence of the environmental temperature on them. Placental area weight records were also maintained and by applying linear regression equation they have been correlated with the birth weight to establish that the birth weight difference was due to the influence of environmental temperature on placental growth and development. Goats were found to be polyoestrous and 61. 54 per cent came into oestrus during the period from April to September when the day is long. Of the two peak breeding activities noticed the greater one occurred in July and the other during November. Breeding activity was found to be low during the months of January and February. The duration of oestrous cycle was found to be 18 – 23 days but the cycle length varied from 6 to 140 days. 45.8 per cent of the animals had an oestrus duration of less than 18 days. Duration of oestrus varied from 12- 48 h. Cessation of oestrus was noticed in 84.8 per cent of animals by 36 h and in 93.26 per cent of animals by 48 h. Conception percentage to first time single and double inseminations during a heat were 33.93 and 42.85 respectively. Overall conception percentages for the above were 71.42 and 82.14 respectively. Average gestation length was 145.62 ± 0.23 days while with singleton, twin and triplet, the durations were 146.05 ± 144.86 ± 0.32 and 145.25 ± 1.03 days. In twin pregnancies and in pregnancies with male foetus/foetuses in both singleton and homogamous twin, was found to have lesser duration of gestation. Mean durations of the first, second and third stages of labour were 57.47 ± 10.29 , 14.52 ± 1.34 and 128.87 ± 4.84 min respectively. Presentation of kids at the time of birth was 88.9 per cent in anterior and the rest in posterior presentation. Secondary sex ratios of singleton and multiple pregnancies were 52.05 and 54.08 per cent with an overall of 53.22 per cent. No significant variation could be observed in the secondary sex ratio of kids those were conceived between seasons having variable environmental temperature. Mean birth weight of kids born during the three trimesters with mean environmental maximum temperature 39.0, 33.4 and 36.30 C were respectively 1.64, 1.92 and 1.88 kg. Between the trimesters having 39. 00 C and 33.40 C there was a significant increase in birth weight. A definite correlation was found to exist between the placental weight and birth weight and the placental area and birth weight. The following conclusions were derived : 1. There is a reproductive pattern difference as could be seen from the above as 61.54 per cent of the oestruses occurred during the period of long days, contrary to the belief that breeding season of goats is the short days. Peak breeding activity was also noticed during the month of July. An instinctive attempt to reduce the number of births during the months of heavy rain which is not conducive for the survival of the young could be appreciated from the low breeding activity seen during January and February. 2. The duration of oestrous cycle, oestrus, gestation and the first, second and third stages of parturition were found to be in consonance with the already available informations. 3. Two inseminations during a heat was found to improve the conception percentage over single insemination. 4. Incidence of multiple pregnancy was found to be lower in the flock. 5. Secondary sex ratio of the kids born was 53.22 per cent and it confirms well with the reports already available. Presentation of foetus was anterior in 88.9 per cent and the rest of posterior presentation. 6. Conception between periods of variable environmental temperature did not seem to influence the sex ratio, to significantly alter the secondary sex ratio. 7. Environmental temperature at the time of conception was found to significantly influence the birth weight of kids. From the correlation that could be established between placental weight and birth weight and between placental area and birth weight it could be inferred that the environmental temperature effect on birth weight is through its influence on placental development and growth.